Fibroblasts: the cellular choreographers of wound healing - Knoedler, Samuel; Broichhausen, Sonja; Guo, Ruiji; Dai, Ruoxuan; Knoedler, Leonard; Kauke-Navarro, Martin; Diatta, Fortunay; Pomahac, Bohdan; Machens, Hans-Guenther; Jiang, Dongsheng; Rinkevich, Yuval (Frontiers in immunology, 2023)
Injuries to our skin trigger a cascade of spatially- and temporally-synchronized healing processes. During such endogenous wound repair, the role of fibroblasts is multifaceted, ranging from the activation and recruitment of innate immune cells through the synthesis and deposition of scar tissue to the conveyor belt-like transport of fascial connective tissue into wounds. A comprehensive understanding of fibroblast diversity and versatility in the healing machinery may help to decipher wound pathologies whilst laying the foundation for novel treatment modalities. In this review, we portray the diversity of fibroblasts and delineate their unique wound healing functions. In addition, we discuss future directions through a clinical-translational lens.
Gesehen am 11.10.2023